2020
DOI: 10.1002/cncr.33329
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported symptom severity, interference with daily activities, and adverse events in older and younger women receiving chemotherapy for early breast cancer

Abstract: Background To the authors' knowledge, it is unknown whether patient‐reported symptom severity and symptom interference with daily activities differ between younger (aged <65 years) and older (aged ≥65 years) women receiving similar chemotherapy regimens for early breast cancer (EBC). Methods Study participants rated 17 side effects of chemotherapy regimens currently in use in clinical practice (2014‐2019). Results Of 284 women with EBC (stage I‐III), approximately 57% were aged <65 years and 43% were aged ≥65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Another possible reason is the treatment-related side effects brought by the anticancer treatment itself. Previous studies found that the treatment adverse reactions are also a major source of symptom burden, 30 , 31 , 32 especially the burden of somatic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason is the treatment-related side effects brought by the anticancer treatment itself. Previous studies found that the treatment adverse reactions are also a major source of symptom burden, 30 , 31 , 32 especially the burden of somatic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…All of these variables provide a context for the observed associations of SVI with symptom experience prior to chemotherapy and during chemotherapy, as well as how these symptoms interfere with the patient's activities of daily living. These SVI ndings provide added context to our prior studies in which we have reported symptom experiences between patient with high as compared to normal BMI [34], Black and White patients[8], and younger as compared to older patients [35]. SVI adds geography to the patient pro le.…”
Section: Discussionmentioning
confidence: 70%
“…Both formats inquire about symptom "severity" and "interference with daily activities" with response options none, mild, moderate, severe or very severe. Data collected from both instruments have been combined, as in our previous studies [9,[30][31][32].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, systemic cancer treatment, including chemotherapy, was administered to 247,939 patients in 2016, representing a 25% increase since 2012 [1]. Chemotherapy frequently causes physical side efects [2], with more than 75% of Australians undergoing chemotherapy for cancer reporting multiple moderate or severe side efects [3]. Individuals with cancer also commonly experience psychosocial and emotional challenges during treatment [4,5].…”
Section: Introductionmentioning
confidence: 99%